Assessing the Impact and Phasing of Multi-year Fiscal Adjustment : A General Framework - Bi, Ran (IMF Working Papers; Working Paper ;, 2013)
This paper provides a general framework to assess the output and debt dynamics of an economy undertaking multi-year fiscal adjustment. The framework allows country-specific assumptions about the magnitude and persistence of fiscal multipliers, hysteresis effects, and endogenous financing costs. In addition to informing macro projections, the framework can also shed light on the appropriate phasing of fiscal consolidation-in particular, on whether it should be front- or back-loaded. The framework is applied to stylized advanced and emerging economy examples. It suggests that for a highly-indebted economy undertaking large multi-year fiscal consolidation, high multipliers do not always argue against frontloaded adjustment. The case for more gradual or back-loaded adjustment is strongest when hysteresis effects are in play, but it needs to be balanced against implications for debt sustainability. Application to actual country examples tends to cast doubt on claims that very large multipliers have been operating post-crisis. It seems that the GDP forecast errors for Greece may have been due more to over-optimism on potential growth estimates than to underestimating fiscal multipliers.